(untitled) (Nigerian Journal of Technology, 2009)
To acquiesce to the request of man’s need to protect his life, investment, property and to maintain law and order in a society, security systems are employed to achieve these goals. For the effective realization of these goals, the system must be able to incorporate different functions and monitor several activities instantaneously in real time. These activities include access control, motion detection, fire hazard and the ease of monitoring the system via the Internet. The system has a way of monitoring requests for access to the secured areas as well as reacting to intruder attempts. To achieve this, a successful hardware data acquisition unit based on a microcontroller is designed. The data from the hardware unit is connected to the PC via the parallel port interface so as to monitor all status signals in real time. The GUI provides graphic display of the trends from the sensor devices.